The impact of autopsy participation on clinical residency. (3rd May 2021) - Katayama, Kohta; Nishizaki, Yuji; Shinozaki, Tomohiro; Saitoh, Yuta; Yano, Tetsuhiro; Aoki, Takuya; Noguchi, Masayuki; Tokuda, Yasuharu
Abstract: Background: Autopsy has had an essential role in ensuring the quality of education and medical care. However, its role in clinical residency has not been clarified. This study assessed actual autopsy circumstances during clinical residency and evaluated the association between autopsy and clinical knowledge. Methods: We conducted a cross‐sectional study involving postgraduate second year residents in Japan who took the General Medicine In‐Training Examination in 2019. We modeled the General Medicine In‐Training Examination scores of the residents to examine their association with autopsy experiences and the number of autopsy experiences to assess its predictors. Results: Of 2715 postgraduate second year residents, 353 (13.8%) had no autopsy participation, and 1015 (39.7%) had only one experience. Although autopsy participation was not related to the mean General Medicine In‐Training Examination score, the residents' clinicopathological conference participation, self‐study for more than 60 min per day, and wish to be pathologists were significantly associated with autopsy experiences. They experienced more autopsies when they belonged to small‐sized hospitals in rural areas performing many autopsies. Conclusion: We reported the current status of autopsy in clinical residency and showed that more than half of the residents experienced no or only one autopsy. General Medicine In‐Training Examination scores were not correlated with the number of autopsy experiences. Abstract : We reported that more than half of resident physicians experienced no or only 1 autopsy. Although General Medicine In‐Training Examination scores were not correlated with the number of autopsy experiences, highly motivated residents in a rural area experienced more autopsies. ​